Bronze Bull Found in Israelite "High Place" from the Time of the Judges - Mazar, ʿAmiḥai (The Biblical archaeology review, 1983)
When he found it, Ofer Broshi was on army duty. Army life can be exhausting or boring—or sometimes both. At that moment, Broshi, a rugged young kibbutznik, was more bored than tired. He was resting on the summit of a hill in northern Samaria, above the ancient road connecting the Biblical towns of Dothan […]